1989
DOI: 10.1128/jb.171.11.6367-6371.1989
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the recA analog from the marine fish pathogen Vibrio anguillarum 775

Abstract: The recA analog from Vibrio anguillarum 775 was isolated by complementation of recA mutations in Escherichia coli, and its protein product was identified. The recA analog promoted recombination between two partially deleted lactose operons, stimulated both spontaneous and mitomycin C-induced phage production in RecA-lambda lysogens, and restored near wild-type levels of resistance to UV radiation and methyl methanesulfonate.The Escherichia coli RecA protein is required for recombination (11,17,32,(35)(36)(37)4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
4
16
0
Order By: Relevance
“…tuberculosis recombinant plasmid were sensitive when exposed to short-wavelength UV radiation. Similar results were observed for the cloned recA homologues from the Gram-negative bacterium Vibrio anguillarum (Singer, 1989) and the obligate anaerobe Bacteroides fragilis (Goodman et al, 1987). The results obtained with Vibrio anguillarum indicate that complementation becomes less efficient when doses of UV radiation are higher.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…tuberculosis recombinant plasmid were sensitive when exposed to short-wavelength UV radiation. Similar results were observed for the cloned recA homologues from the Gram-negative bacterium Vibrio anguillarum (Singer, 1989) and the obligate anaerobe Bacteroides fragilis (Goodman et al, 1987). The results obtained with Vibrio anguillarum indicate that complementation becomes less efficient when doses of UV radiation are higher.…”
Section: Discussionsupporting
confidence: 76%
“…Sancar et al (1980) found the E. coli recA gene product to be a single polypeptide with a calculated molecular mass of 37.8 kDa. Genes encoding RecA-like activity have been cloned from many Gram-negative bacteria, including Pseudomonas aeruginosa (Kokjohn & Miller, 1985), Shigella flexneri (Keener et al, 1984), Vibrw anguillarum (Singer, 1989), Proteus vulgaris (Keener et al, 1984), Agrobacterium tumefaciens (Farrand et al, 1989) and Haemophilus influenzae (Setlow et al, 1988). However, there has been only one report of isolation from a Gram-positive organism, namely Bacillus subtilis (Marrero & Yasbin, 1988), and to date there has been no report of the cloning of a recA gene from a member of the Actinomycetes.…”
Section: Introductionmentioning
confidence: 99%
“…Genes in the ivi region are believed to play a role in virulence mechanisms, phospholipase signalling, genetic regulation, metabolism and outermembrane assembly, but such functions are left only to speculation at the present time and more research in this area is likely to emerge in future studies (Zou et al 2010). Furthermore, the gene recA is expressed to repair damaged DNA and the gene is required for recombination but not survival (Singer 1989;Singer et al 1996).…”
Section: Bacteriology and Stress Survivalmentioning
confidence: 99%
“…In contrast to the established way of cloning recA-like genes by interspecies complementation of E. coli recA mutations (e.g. Better and Helinski 1983;Goldberg and Mekalanos 1986;Koomey and Falkow 1987;Berson et al 1989;Singer 1989), identification and subcloning of the M. clara recA gene was performed by hybridization analysis.…”
Section: Discussionmentioning
confidence: 99%
“…No difference can be observed between the amino acid sequences of various functional domains that have been identified by either structural and functional analyses of E. coli recA gene mutations (Kawashima et al 1984;Wang and Tessman 1985;Ogawa and Ogawa 1986). As an example, the nucleotide sequence of the putative ATP-binding site (Gly 65 to Thr 72) of the E. coli RecA protein is completely conserved in its P. aeruyinosa and M. clara homologues, as well as in the recently published recA genes from Aquaspirillum tnaonetotacticum (Berson et al 1990) and Vibrio anouillarum (Singer 1989). The high similarity is further confirmed by the results of overexpression and protein-labelling studies showing the production of a 37-kDa polypeptide, as well as by complementation analysis of UV-irradiation-sensitive E. coli recA mutants.…”
Section: Discussionmentioning
confidence: 99%